Protein folding of the SAP domain, a naturally occurring two‐helix bundle. Issue 15 (11th June 2015) - Dodson, Charlotte A.; Arbely, Eyal
Abstract : The SAP domain from the Saccharomyces cerevisiae Tho1 protein is comprised of just two helices and a hydrophobic core and is one of the smallest proteins whose folding has been characterised. Φ‐value analysis revealed that Tho1 SAP folds through a transition state where helix 1 is the most extensively formed element of secondary structure and flickering native‐like core contacts from Leu35 are also present. The contacts that contribute most to native state stability of Tho1 SAP are not formed in the transition state. Abstract : Thol SAP domain is one of the smallest model protein folding domains. SAP domain folds through a diffuse transition state in which helix 1 is most formed. Native state stability is dominated by contacts formed after the transition state.